(3eYGde GdJfRjds - (3CMeO Hf jhSa Hf eSYhO GdaQGA GdHZhj GdMdHjs
(3ChdgG (B:s
(3bhdg YR hLd (B( (3hbd ddeDefGJ jZVVf ef CHUGQgf (B) (3YeG dG jMd hjMaXf aQhLgf YeG dG jMd hbjd CjVkG jMaXf aQhLgf Ci jSJQgG MJi dGjQGgG CMO s
(3BNQgG (B:s
(3Yf CHj gQjQI QVi Gddg Yfg bGd bGd QShd Gddg Udi Gddg Ydjg hSde jbhd Gdgd YR hLd (B:- ( (3GdcHQjGA RGOi hGdYXeI ERGQi aef fGRYfi hGMOkG efgeG CONdJg GdfGQ ced GdLRA GdNGeS HMeO Gddg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG hbajI hJMHjS HGSe MSf HGTG YHO GdQGRbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1726s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs